False conclusion - Heley, Veronica (Heley, Veronica. Abbot Agency, 2020)
"Bea Abbot is looking forward to spending the summer with her fourteen-year-old ward, Bernice, but her plans go awry when one of Bernice's schoolfriends finds herself in trouble. Evelina Trescott's uncle has died in a mysterious accident at their country house, and her aunt, Mrs Trescott, is keen to hide Evelina away from the police. Evelina arrives on Bea's doorstep catatonic, heavily drugged up on epilepsy medication and unable to remember finding her uncle's body. Is she really a hapless victim, or is Bea harbouring a wily criminal? The more Bea learns about the troublesome Trescotts, the more she realizes something is horribly wrong, and soon finds herself drawn into a dark web of greed, abuse, and murder."--